Degradation in aluminum resonant optical rod antennas. Issue 1728 (5th February 2015) - Schwab, Patrick M.; Moosmann, Carola; Dopf, Katja; Ilin, Konstantin S.; Siegel, Michael; Lemmer, Uli; Eisler, Hans-Juergen
ABSTRACT: Resonant optical rod antennas are made from aluminum using electron-beam lithography and are optically characterized by linear dark-field microscopy and nonlinear multi-photon luminescence spectroscopy. It is demonstrated that by exciting close to the interband transition of aluminum at about 1.5 eV different radiative decay channels can be addressed. Over a period of weeks, a slight spectral red-shift and a decrease in the scattering intensity are observed due to the formation of a native oxide layer at the metal-air interface. To investigate the concurrent influence of shape transformation and dielectric environment on the spectral response function we carry out numerical calculations using finite difference time domain (FDTD) methods. It is found that the induced energy shift is mainly determined by the change of the dielectric constant in the nanovicinity resulting in an overall red-shift as seen in the experiment. These findings allow for a better understanding of designing and modeling plasmonic aluminum nanostructures for e.g. UV sensing where the shift in peak resonance and linewidth are key observables.